THE INFLUENCE OF ATTACHMENT AND QUALITY OF PARENTING AND PARENTING ENVIRONMENT ON CHILDREN’S CHARACTER IN RURAL AND URBAN AREAS OF BOGOR - Dewanggi, Mustika; Hastuti, Dwi; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2015)
This study aimed to analyze the influence of attachment, environmental quality of parenting (HOME), and parental acceptance rejection -as indicator of quality of parenting- on preschool children’s character in rural and urban areas of Bogor. The population of the study was intact families with the eldest child aged 3-6 years and lives together with the parents. The sample of this research was selected by simple random sampling (n=100,50% live in rural area). The result showed that the average score of attachment in rural areas was higher than inurban areas. There was a significant difference of maternal attachment between participants in rural and urban area. The average score of the environmental quality of parenting in rural was higher than in urban area, while the verage score of parental acceptance-rejection in rural area was lower than in urban area. Average score of children’s character in urban area was higher and significantly different compared to participants in urban area. Regression analysis showed that the child's sex, child’s age, mother’s age, and attachment were significantly associated with the character of the child.